Performance evaluation of rigid pavements in Costa Rica - Montes de Oca Hidalgo, María Paula (2025)
The need to understand the typical deterioration of rigid pavements in Costa Rica is recognized, since there are no design techniques or information at a constructive level that considers the country's climatological and traffic variables. To complement the existing information, an evaluation is proposed to determine the typical deterioration of rigid pavements in Costa Rica. The evaluation of rigid pavements was based on a visual auscultation and an automatic survey using Geo 3D. Initially, the deterioration of each of the seven projects was surveyed and used to calculate their PCI (Pavement Condition Index) and to determine the typical deterioration. Then, the climatological and traffic characteristics of each project were identified and related to the deteriorations. Finally, the relationships obtained were used to create the initial deterioration prediction models. It was observed that the typical deteriorations in Costa Rica are joint seal damage (21,22 %), aggregate spalling (13,58 %), aggregate polishing (13,10 %) and linear cracking (7,08 %). In addition, the deteriorations are related to precipitation, temperature, and equivalent axis. Therefore, it is recommended that the results of this research serve as a basis for future deterioration prediction models.